PEMATUHAN SYARIAH DALAM OPERASI TAKAFUL DI BAWAH AKTA PERKHIDMATAN KEWANGAN ISLAM (APKI) 2013: Shariah Compliance of the Operation of Takaful under the Islamic Financial Services Act 2013 - Hasan, Rusni; Salleh, Safinar (Jurnal Syariah, 2017)
The enforcement of the Islamic Financial Services Act 2013 (IFSA) brought many changes to the Islamic finance industry in Malaysia, especially in regards to Shariah compliance. The Act emphasises Shariah-compliant requirements which must be fulfilled by all Islamic financial insitutions (IFIs). The enhancement of this feature by the IFIs may increase public confidence and ensure stability in the Islamic financial system, including takaful. With regard to the latter, several improvements have been made in IFSA in respect to the insufficienies of the Takaful Act 1984 by incorporating new provisions including those related to Shariah. This article aims to examine the impact of the Act on Shariah compliance in the operation of takaful. This study is qualitative and uses a traditional legal research method to analyse the Shariah compliance requirements in the provisions of IFSA relating to takaful. This study found that the improvements made to the Act are essentially in compliance to the Shariah, but several issues may arise from some provisions of the Act. Thus, further research should be done to resolve these issues.